Composite material battery box and preparation method thereof

By applying ablation-resistant coating material inside the battery box, the shortcomings of the carbon fiber battery box in terms of explosion-proof and flame retardant are solved, and higher thermal safety and passenger safe evacuation time are achieved.

CN119764702APending Publication Date: 2025-04-04WUHAN UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411654335.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing carbon fiber battery boxes have shortcomings in explosion-proof and flame retardant, and it is difficult to effectively deal with the combustion and explosion hazards caused by short circuits and high temperatures of the battery pack.

Method used

The inside of the battery box is coated with ablation-resistant coating material, including melting, resin-based and ceramic-based coatings, to increase the combustion temperature of the battery box and reduce oxygen content, and delay the heat spreading speed.

Benefits of technology

It effectively improves the protection effect and thermal safety of the battery pack, provides valuable time for passengers to evacuate safely, and enhances the explosion-proof and flame-retardant capability of the battery box.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764702A_ABST
    Figure CN119764702A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material battery box and a preparation method thereof, and belongs to the technical field of power batteries. The composite material battery box comprises a box body and an upper cover, ablation-resistant coatings are arranged on the inner walls of the box body and the upper cover, and the ablation-resistant coatings are selected from melting type ablation-resistant coatings, resin-based ablation-resistant coatings or ceramic-based ablation-resistant coatings; the melting type ablation-resistant coating comprises fused quartz and / or glass materials, the resin-based ablation-resistant coating comprises silicone rubber, phenolic aldehyde and / or epoxy materials, and the ceramic-based ablation-resistant coating comprises an RCG coating material; according to the utility model, an ablation-resistant coating material is coated inside the battery box and is used for preventing harm caused by factors such as short circuit and high temperature. When the battery cell burns, the ablation-resistant coating material not only can improve the combustion temperature of the battery box, but also can effectively reduce the oxygen content and delay the heat spreading speed, thereby providing precious time for safe evacuation of passengers, and improving the protection effect and the heat safety of the battery pack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of power batteries, and in particular relates to a composite material battery box and a preparation method thereof, and more particularly to a composite material battery box capable of coping with rapid temperature rise due to short circuit. Background Art

[0002] With the development of social economy, new energy vehicles are moving towards green and sustainable development, creating a cleaner, more environmentally friendly and efficient way of travel for mankind. As the direct power source of electric vehicles, the safety performance of power battery packs is particularly important, and this is also one of the important reasons hindering the development of this field. In the prior art, the battery cells are usually placed in a battery box for packaging, and the battery box is required to have high strength and light weight (to ensure mileage). Usually, the material of the battery box is aluminum alloy, which reduces weight while ensuring strength. However, there is already a solution in the prior art to prepare a battery box using carbon fiber materials.

[0003] For example, the patent application number CN202210065848.7 discloses a method for forming a carbon fiber battery box, including box body forming and box cover forming, wherein the box body forming includes the following steps: S1: cutting prepregs according to the shape and size of the box to be formed and the position of the embedded parts inside it, to obtain a prepreg layer on the outer surface of the box, a prepreg layer in the center of the box, a prepreg layer on the inner surface of the box and a pre-embedded prepreg layer, wherein the pre-embedded prepreg layer is used to set the embedded parts, the prepreg layer in the center of the box includes multiple layers of carbon fiber prepreg, and the pre-embedded prepreg layer includes multiple layers of glass fiber prepreg; S2: Lay the outer surface prepreg layer of the box, the center prepreg layer of the box, the inner surface prepreg layer of the box and the embedded prepreg layer according to the set laying method, wherein part of the embedded prepreg layer is spliced ​​with the center prepreg layer of the box, and after the glass fiber prepreg of each layer of the embedded prepreg layer is spliced ​​with the carbon fiber prepreg of each layer of the center prepreg layer of the box, the joints of the two adjacent layers are staggered, and the embedded parts are partially arranged in the glass fiber prepreg of the embedded prepreg layer, and the box preform is obtained after the laying is completed; S3: placing the box preform into a box forming mold, curing and forming the box preform under set conditions, and obtaining a box cured molded body after completion, and taking it out from the box forming mold; S4: post-processing the box body solidification molding to obtain a box body to be formed.

[0004] For example, the patent application number CN201510342040.9 discloses a method for manufacturing a carbon fiber automobile battery box, which includes the following steps: 1) Design of automobile battery box processing mold: the mold flange should be as flat as possible, and the flange width should be at least 150mm, and sharp corners should be avoided in the effective cavity of the mold; 2) In order to ensure the accuracy of the size, epoxy wood and matching white glue are selected as the materials for making the car battery box model. The car battery box model is added according to the product data 1:1 and trimmed according to the size requirements; 3) Automobile battery box mold making: Coat the surface of the automobile battery box model with release wax and release agent, then spray the gel coat evenly, then use surface felt and epoxy resin to make the surface layer of the cavity of the automobile battery box mold, and then use chopped felt and mold resin to make the main body of the automobile battery box mold. After curing, demould and grind and polish the surface of the cavity of the automobile battery box mold; 4) Material preparation: The gel coat selected must be resistant to 120°C to cope with the heat release of each mold product. The thickness of the gel coat layer for preparing the automotive battery box should not be less than 0.6mm. The resin selected for preparing the automotive battery box requires an epoxy-modified vinyl resin with a shrinkage rate of essentially zero; the carbon fiber cloth should be carbon fiber plain cloth; 5) Production of automobile battery box: Coat the mold release agent on the cavity surface of the automobile battery box mold and spray the gel coat layer, lay the carbon fiber cloth with 3M spray glue, place the auxiliary tools and then evacuate, then introduce the epoxy modified vinyl resin, demould after curing, trim and punch the product according to the drawing, and spray the inner surface with insulating paint.

[0005] Carbon fiber is lighter than aluminum, but its safety is difficult to guarantee. The safety of the battery pack includes dustproof, impact-proof, heat-proof, explosion-proof and flame-retardant aspects, among which the protection requirements for explosion-proof and flame-retardant are getting higher and higher. On the one hand, a large degree of disaster is prone to occur when the battery pack burns and explodes; on the other hand, the battery pack cells are easily affected by factors such as short circuits and high temperatures, which cause high-temperature airflow inside the battery pack, causing combustion and explosion. However, carbon fiber is not burn-resistant and is actually not suitable for battery use scenarios. Its explosion-proof and flame-retardant capabilities are greatly insufficient. Summary of the invention

[0006] In order to solve the above problems, the embodiment of the present invention provides a composite battery box and a preparation method thereof, using an ablation-resistant coating material to coat the interior of the battery box to protect against hazards caused by short circuits, high temperatures and other factors. When the battery cell burns, the ablation-resistant coating material can not only increase the combustion temperature of the battery box, but also effectively reduce the oxygen content, slow down the heat spread rate, provide valuable time for the safe evacuation of passengers, and improve the protection effect and thermal safety of the battery pack. The technical solution is as follows: On the one hand, an embodiment of the present invention provides a composite battery box, including a box body and an upper cover, both of which are made of carbon fiber material. The inner walls of the box body and the upper cover are provided with an ablation-resistant coating, and the ablation-resistant coating is selected from a melting type ablation-resistant coating, a resin-based ablation-resistant coating or a ceramic-based ablation-resistant coating. Among them, the melting type ablation-resistant coating includes fused quartz and / or glass-type materials, the resin-based ablation-resistant coating includes silicone rubber, phenolic and / or epoxy materials, and the ceramic-based ablation-resistant coating includes RCG coating materials. The thickness of the melting type ablation-resistant coating is 2.0-3.0mm, the thickness of the resin-based ablation-resistant coating is 1.6-3.0mm, and the thickness of the ceramic-based ablation-resistant coating is 0.3-0.5mm. The maximum burning resistance of the ablation-resistant coating of this patent is about 1450-1500℃, which can be selected according to actual conditions.

[0007] The composition of the fused quartz material is as follows: 55-65 parts of fused quartz hollow spheres, 32-45 parts of fused quartz fine powder, 0-3 parts of alumina fine powder and 6-10 parts of dimethyl silicone oil by weight. The fused quartz material is attached to the inner wall of the box or the upper cover by a scraping method. When scraping, the viscosity of the fused quartz material is controlled to be 60-70s to control the thickness of the fused quartz material.

[0008] The composition of the silicone rubber material is calculated by weight as follows: 20-40 parts of silane compounds, 30-50 parts of silicon oxide, 15-40 parts of aluminum oxide and 3-5 parts of plasticizer. The silane compound is selected from methyltrioxysilane or vinyltrioxysilane, and the plasticizer is a common plasticizer corresponding to methyltrioxysilane or vinyltrioxysilane. The silicone rubber material is attached to the inner wall of the box or the upper cover by scraping. Before scraping, a primer is applied to the inner wall of the box or the upper cover to improve the adhesion of the silicone rubber. The primer used includes but is not limited to KL-301.

[0009] The RCG coating material is sintered from the following raw materials by weight: 45-55 parts of high silica gel frit, 5-10 parts of alumina and 25-50 parts of irradiant. The high silica gel frit includes 88-98wt% SiO 2 and 2-12wt%B 2 O 3 , the radiation agent is selected from MoSi 2 or Cr 2 O 3 The sintering temperature is 1050-1200°C. The RCG coating material is heated to a molten or semi-molten state and sprayed on the inner wall of the box or upper cover through a high-speed airflow.

[0010] The box body is made of carbon fiber material by hot stamping. Both the box body and the upper cover are made of multiple layers of prepreg, with the number of layers being 3-6.

[0011] Specifically, the prepreg is toughened epoxy prepreg EV201, and its surface density is 200-400g / m 2 Of course, this patent can also use other prepregs or carbon fiber composite materials.

[0012] Preferably, four layers of prepreg EV201 are sequentially laid at 0°, 90°, 90° and 0° and vacuum pressed to obtain a laminate, and the surface density of the prepreg is 200-400g / m 2 ; The box body and the upper cover are obtained by hot stamping the laminate respectively; and then the RCG coating is formed on the inner wall of the box body or the upper cover by thermal spraying, and the thickness of the RCG coating is 0.3-0.5mm. Among them, the RCG coating material is sintered from the following raw materials in parts by weight: 45-55 parts of high silica glaze gel frit, 5-10 parts of alumina and 25-50 parts of radiation agent. Among them, the high silica glaze gel frit includes 88-98wt% SiO 2 and 2-12wt%B 2 O 3 , the radiation agent is selected from MoSi 2 or Cr 2 O 3 Etc., the sintering temperature is 1050-1200℃.

[0013] On the other hand, see Figure 1-2 , an embodiment of the present invention provides a method for preparing a composite material battery box, the method comprising: S1 Preparation of prepreg: cutting the prepreg according to predetermined size.

[0014] S2 laminate preparation: The sheared prepreg is laid in a certain layering sequence and layering angle, and then vacuum bagged (vacuum bagged, vacuumed and tested for air tightness) and pressed to form the required laminate. The vacuum degree of vacuum bag pressing is greater than 0.099MPa, and the pressing time is greater than 30min.

[0015] S3 preheating treatment: take the laminate out of the vacuum bag and preheat the laminate and the mold respectively. Specifically, the preheating temperature of the laminate is 145-155°C and the preheating time is 30-50s. The preheating temperature of the mold is 175-185°C and the preheating time is 45-55s. The preheating method includes but is not limited to preheating in an oven or preheating with a spray gun.

[0016] S4 hot stamping: put the preheated laminate into the preheated mold to prepare the box or cover, close the mold, and then cure; the curing conditions are: curing temperature is 140-165℃, curing time is 240-300s, and curing pressure is 10-25Mpa.

[0017] S5 demoulding: After cooling, the formed box body or upper cover is removed from the mold.

[0018] S6 Preparation of ablation-resistant coating: A ablation-resistant coating is formed on the inner wall of the box body or the upper cover by a scraping method or a thermal spraying method.

[0019] S7 cleaning and polishing: Clean and polish the box or cover.

[0020] Preferably, in step S4, when the mold is closed, a low-pressure rapid mold closing method is adopted when the upper mold is far away from the laminate, and a high-pressure slow mold closing method is adopted when the upper mold starts to contact the laminate; the pressure required for the low-pressure rapid mold closing is 1.5-3.0Mpa, and the pressure required for the high-pressure rapid mold closing is 15-30MPa.

[0021] Specifically, in step S6, the inner wall of the box is first cleaned and polished, and then the ablation-resistant coating is formed by one of the following methods: First, apply the primer on the inner wall of the box or the upper cover, and then use the scraping method to attach the silicone rubber material to the inner wall of the box or the upper cover. After the scraping is completed, place it at 120-150℃ for 20-30s to cure.

[0022] Alternatively, the fused quartz material is attached to the inner wall of the box or the upper cover by a scraping method. The viscosity of the fused quartz material is controlled to be 60-70s during scraping. After the scraping is completed, it is allowed to stand at room temperature for 60-80s for solidification.

[0023] Alternatively, the RCG coating material may be attached to the inner wall of the box or the upper cover by spraying without curing.

[0024] More specifically, step S6 includes: S601: Prepare coating materials and automatic scraping equipment. The automatic scraping equipment includes scraping robot arm, paint delivery system and control system, etc.

[0025] S602: Set the process parameters of the scraping equipment. The setting of parameters will affect the uniformity and thickness of the coating. The process parameters include movement speed, coating flow rate and scraping pressure.

[0026] S603: Perform surface pretreatment. Before coating, the surface of the workpiece needs to be cleaned and polished. Surface pretreatment methods include but are not limited to mechanical cleaning, chemical cleaning or sandblasting.

[0027] S604: Automatic scraping or spraying. The robot arm will take out the paint and then scrape or spray along the surface of the workpiece to avoid coating defects.

[0028] S605: Monitor the quality of the coating so as to adjust and process the process parameters in a timely manner. Monitoring technologies include but are not limited to online monitoring and image recognition.

[0029] S606: After the coating is completed, it is cured to improve its heat resistance and adhesion. The curing time and curing temperature required for curing are adjusted according to the requirements of the coating and equipment.

[0030] S607: Perform quality monitoring on the properties and quality of the coating. Monitoring techniques include but are not limited to chemical analysis and physical testing.

[0031] The technical solution provided by the embodiment of the present invention has the following beneficial effects: (1) The strength of the processed carbon fiber box meets the use requirements, with high dimensional accuracy and good repeatability, and can basically achieve semi-automatic production.

[0032] (2) The method for preparing the carbon fiber composite battery box of the present invention uses an ablation-resistant coating material, which is beneficial to protecting the safe evacuation of passengers and has high safety. Specifically, the ablation-resistant coating material can not only increase the combustion temperature of the battery box, but also effectively reduce the oxygen content, slow down the heat spread rate, provide valuable time for the safe evacuation of passengers, and improve the protection effect and thermal safety of the battery pack.

[0033] (3) For RCG coating materials, the coating thickness is thin (the thickness is 0.3-0.5mm, usually 0.3-0.4mm, which basically does not increase the weight and basically does not occupy the internal space of the box), the processing is simple (it can be sprayed), and no curing is required.

[0034] (4) The applicant selected a material suitable for carbon fiber and battery box from a large number of ablation-resistant coating materials. The material has the advantages of low density, no effect on the strength of carbon fiber, fire resistance suitable for use in battery boxes (the highest fire resistance is about 1450-1500°C), and no effect on carbon fiber during the curing process (low curing temperature and short time). BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a flow chart of a method for preparing a composite material battery box in an embodiment of the present invention; Figure 2 is a process diagram of a method for preparing a box body in an embodiment of the present invention; Among them, 1 carbon fiber prepreg, 2 carbon fiber laminate, 3 heating device, 4 hot stamping die, 5 molded parts, 6 silicone rubber heat-resistant coating scraping device, 7 part edge structure. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0037] Example 1 Embodiment 1 provides a method for preparing a composite material battery box, comprising the following steps: S1 Preparation of prepreg: Prepreg EV201 is cut according to the predetermined size. The surface density of prepreg EV201 is 310g / m 2 Specifically, the size of the prepreg required for the upper cover is 600mm*500mm; the size of the prepreg required for the box body is 900mm*800mm.

[0038] Preparation of S2 laminate: Four layers of prepreg are stacked in sequence at 0°, 90°, 90° and 0° and vacuum pressed to obtain a laminate, which is then vacuum bag pressed to form the desired laminate; the vacuum degree of vacuum bag pressing is greater than 0.099MPa, and the pressing time is greater than 30min.

[0039] S3 preheating treatment: take the laminate out of the vacuum bag and preheat the laminate and the mold separately. The preheating temperature of the laminate is 150°C and the preheating time is 45s; the preheating temperature of the mold is 180°C and the preheating time is 50s.

[0040] S4 hot stamping: put the preheated laminate into the preheated mold to prepare the box or cover, close the mold, and then cure; the curing conditions are: curing temperature is 150°C, curing time is 250s, and curing pressure is 20Mpa.

[0041] S5 demoulding: remove the molded box or cover from the mold.

[0042] Preparation of S6 ablation-resistant coating: First, clean and polish the inner wall of the box, then apply primer on the inner wall of the box or the upper cover, and then use the scraping method to attach the silicone rubber material to the inner wall of the box or the upper cover. After the scraping is completed, place it at 125°C for 25 seconds for curing. Among them, the composition of the silicone rubber material is calculated by weight: 30 parts of vinyl trioxy silane, 35 parts of silicon oxide, 20 parts of aluminum oxide and 5 parts of plasticizer.

[0043] S7 cleaning and polishing: Clean and polish the box or cover.

[0044] The size of the upper cover is 320mm*260mm*50mm, the size of the box is 320mm*260mm*200mm, and the thickness of the ablation-resistant coating is 2mm.

[0045] Example 2 Embodiment 2 provides a method for preparing a composite material battery box, comprising the following steps: S1 Preparation of prepreg: Prepreg EV201 is cut according to the predetermined size. The surface density of prepreg EV201 is 310g / m 2 Specifically, the size of the prepreg required for the upper cover is 600mm*500mm; the size of the prepreg required for the box body is 900mm*800mm.

[0046] Preparation of S2 laminate: Four layers of prepreg are stacked in sequence at 0°, 90°, 90° and 0° and vacuum pressed to obtain a laminate, which is then vacuum bag pressed to form the desired laminate; the vacuum degree of vacuum bag pressing is greater than 0.099MPa, and the pressing time is greater than 30min.

[0047] S3 preheating treatment: take the laminate out of the vacuum bag and preheat the laminate and the mold separately. The preheating temperature of the laminate is 150°C and the preheating time is 45s; the preheating temperature of the mold is 178°C and the preheating time is 50s.

[0048] S4 hot stamping: put the preheated laminate into the preheated mold to prepare the box or cover, close the mold, and then cure; the curing conditions are: curing temperature is 155°C, curing time is 250s, and curing pressure is 22Mpa.

[0049] S5 demoulding: remove the molded box or cover from the mold.

[0050] Preparation of S6 ablation-resistant coating: The fused quartz material is attached to the inner wall of the box or the upper cover by scraping, and the viscosity of the fused quartz material is controlled to be 60-70s during scraping. After scraping, it is left to stand for 75s at room temperature for solidification. The composition of the fused quartz material is calculated by weight: 58 parts of fused quartz hollow spheres, 40 parts of fused quartz fine powder, 1 part of alumina fine powder and 7 parts of dimethyl silicone oil.

[0051] S7 cleaning and polishing: Clean and polish the box or cover.

[0052] The size of the upper cover is 320mm*260mm*50mm, the size of the box is 320mm*260mm*200mm, and the thickness of the ablation-resistant coating is 2.4mm.

[0053] Example 3 Embodiment 3 provides a method for preparing a composite material battery box, comprising the following steps: S1 Preparation of prepreg: Prepreg EV201 is cut according to the predetermined size. The surface density of prepreg EV201 is 310g / m 2 Specifically, the size of the prepreg required for the upper cover is 600mm*500mm; the size of the prepreg required for the box body is 900mm*800mm.

[0054] Preparation of S2 laminate: Four layers of prepreg are laid in order at 0°, 90°, 90° and 0° and vacuum pressed to obtain a laminate. The laminate is then formed into the desired laminate by vacuum bag pressing; the vacuum degree of vacuum bag pressing is greater than 0.099MPa, and the pressing time is greater than 30min.

[0055] S3 preheating treatment: take the laminate out of the vacuum bag and preheat the laminate and the mold separately. The preheating temperature of the laminate is 155°C and the preheating time is 35s; the preheating temperature of the mold is 180°C and the preheating time is 52s.

[0056] S4 hot stamping: the preheated laminate is placed in a preheated mold to prepare a box or a cover, the mold is closed, and then cured; the curing conditions are: the curing temperature is 155°C, the curing time is 270s, and the curing pressure is 18Mpa.

[0057] S5 demoulding: remove the molded box or cover from the mold.

[0058] Preparation of S6 ablation-resistant coating: The RCG coating material is attached to the inner wall of the box or the upper cover by spraying, and no curing is required. The RCG coating material is sintered by the following raw materials in parts by weight: 50 parts of high-silica glaze gel frit, 6 parts of alumina and MoSi 2 32 parts. Among them, the high silica glaze gel frit includes 90wt% SiO 2 and 10wt%B 2 O 3 The sintering temperature is 1120°C. The RCG coating material is heated to a molten or semi-molten state and sprayed on the inner wall of the box or upper cover through a high-speed airflow.

[0059] S7 cleaning and polishing: Clean and polish the box or cover.

[0060] The size of the obtained upper cover is 320mm*260mm*50mm, the size of the box is 320mm*260mm*200mm, and the thickness of the ablation-resistant coating is 0.38mm.

[0061] Verification test 1. Battery pack mechanical impact test In order to verify the ability of the prepared battery pack to resist deformation and damage under different working conditions, the stress obtained from the mechanical impact test is used to determine whether the ability of the battery pack to resist mechanical impact loads meets the national standard requirements.

[0062] The mechanical shock test is carried out in accordance with the provisions of GB / T 31467.3-2017 "Lithium-ion power battery packs and systems for electric vehicles Part 3: Safety requirements and test methods", applying a 25g, 15ms half-sine shock wave to the battery pack, impacting the z-axis direction three times, and observing for 2 hours.

[0063] The stress changes during the impact process were recorded by force sensors and displacement sensors, and the maximum stress value was analyzed. The battery box with fused quartz coating material (from Example 2) was subjected to a maximum stress of 590.1 MPa, the battery box with silicone rubber ablation-resistant coating material (from Example 1) was subjected to a maximum stress of 578.3 MPa, and the battery box with RCG ablation-resistant coating material (from Example 3) was subjected to a maximum stress of 582.9 MPa, which were all far less than the maximum tensile strength of the material of 2500 MPa.

[0064] The above mechanical impact test shows that the carbon fiber composite battery box has no leakage, shell rupture, fire or explosion.

[0065] 2. Battery pack fire test In order to verify the ability of the prepared battery pack to withstand fire, the battery pack fire test was used to determine whether it met the national standard requirements. The test objects were carbon fiber composite battery boxes with different ablation-resistant coatings (two were selected for each of Examples 1-3).

[0066] During the test, the size of the flat plate containing gasoline was set to exceed the horizontal size of the test object by 20 cm and not exceed 50 cm. The distance between the gasoline liquid surface and the test object was set to 50 cm.

[0067] Ignite gasoline at least 3m away from the device under test. After 60s of preheating, place the oil pan inside the battery pack box through a mechanical gripper and then place the battery pack box cover. Let the oil pan burn inside the battery box to simulate the effect of a battery short circuit. Remove the oil pan after 70s and observe for 2h.

[0068] Through the above-mentioned fire test, it is found that the carbon fiber composite material battery box prepared by the present invention has no explosion phenomenon and no flame is generated.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite material battery box, comprising a box body and an upper cover, wherein the box body and the upper cover are both made of carbon fiber material; characterized in that: The inner walls of the box body and the upper cover are both provided with ablation-resistant coatings, and the ablation-resistant coatings are selected from melting-type ablation-resistant coatings, resin-based ablation-resistant coatings or ceramic-based ablation-resistant coatings; Among them, the melting type ablation-resistant coating includes fused quartz and / or glass materials, the resin-based ablation-resistant coating includes silicone rubber, phenolic and / or epoxy materials, and the ceramic-based ablation-resistant coating includes RCG coating materials; the thickness of the melting type ablation-resistant coating is 2.0-3.0 mm, the thickness of the resin-based ablation-resistant coating is 1.6-3.0 mm, and the thickness of the ceramic-based ablation-resistant coating is 0.3-0.5 mm.

2. The composite material battery box according to claim 1, characterized in that: The composition of the fused quartz material is calculated by weight as follows: 55-65 parts of fused quartz hollow spheres, 32-45 parts of fused quartz fine powder, 0-3 parts of alumina fine powder and 6-10 parts of dimethyl silicone oil; the fused quartz material is attached to the inner wall of the box or the upper cover by a scraping method, and during the scraping, the viscosity of the fused quartz material is controlled to be 60-70s.

3. The composite material battery box according to claim 1, characterized in that: The silicone rubber material is composed of 20-40 parts by weight of a silane compound, 30-50 parts of silicon oxide, 15-40 parts of aluminum oxide and 3-5 parts of a plasticizer, wherein the silane compound is selected from methyltrioxysilane or vinyltrioxysilane; the silicone rubber material is attached to the inner wall of the box or the upper cover by a scraping method, and before scraping, a primer is first applied to the inner wall of the box or the upper cover.

4. The composite material battery box according to claim 1, characterized in that: The RCG coating material is sintered from the following raw materials in parts by weight: 45-55 parts of high silica glaze gel frit, 5-10 parts of alumina and 25-50 parts of radiation agent; Wherein, the high silica glaze gel frit comprises 88-98wt% SiO2 and 2-12wt% B2O3, the radiant is selected from MoSi2 or Cr2O3, and the sintering temperature is 1050-1200°C; The RCG coating material is heated to a molten or semi-molten state and sprayed onto the inner wall of the box body or the upper cover through a high-speed airflow.

5. The composite material battery box according to claim 1, characterized in that: The box body is formed by hot stamping of carbon fiber material in one piece; the box body and the upper cover are both formed by plying multiple layers of prepreg, with the number of ply layers being 3-6.

6. The composite material battery box according to claim 5, characterized in that: The prepreg is toughened epoxy prepreg EV201, and its surface density is 200-400g / m 2 .

7. The composite material battery box according to claim 1, characterized in that: Four layers of prepreg EV201 are laid in sequence at 0°, 90°, 90° and 0° and vacuum pressed to obtain a laminate. The surface density of the prepreg is 200-400g / m 2 ; The box body and the upper cover are obtained by hot stamping the laminate, and then an RCG coating is formed on the inner wall of the box body or the upper cover by thermal spraying, wherein the thickness of the RCG coating is 0.3-0.5 mm; The RCG coating material is sintered from the following raw materials in parts by weight: 45-55 parts of high silica glaze gel frit, 5-10 parts of alumina and 25-50 parts of radiation agent; wherein the high silica glaze gel frit comprises 88-98wt% SiO2 and 2-12wt% B2O3, the radiation agent is selected from MoSi2 or Cr2O3, and the sintering temperature is 1050-1200°C.

8. A method for preparing a composite material battery box, characterized in that: The method comprises: S1 Prepreg preparation: cutting the prepreg according to a predetermined size; S2 laminate preparation: laying the sheared prepreg in a certain ply order and ply angle, and then performing vacuum bag pressing to form the required laminate; the vacuum degree of the vacuum bag pressing is greater than 0.099MPa, and the pressing time is greater than 30min; S3 preheating treatment: take the laminate out of the vacuum bag, and preheat the laminate and the mold respectively; the preheating temperature of the laminate is 145-155°C, and the preheating time is 30-50s; the preheating temperature of the mold is 175-185°C, and the preheating time is 45-55s; S4 hot stamping: put the preheated laminate into the preheated mold to prepare the box or cover, close the mold, and then cure; the curing conditions are: curing temperature is 140-165℃, curing time is 240-300s, and curing pressure is 10-25Mpa; S5 demoulding: taking the formed box body or upper cover out of the mold; S6 Preparation of ablation-resistant coating: forming ablation-resistant coating on the inner wall of the box body or the upper cover by scraping or thermal spraying; S7 cleaning and polishing: Clean and polish the box or cover.

9. The method according to claim 8, characterized in that In step S4, when the mold is closed, when the upper mold is far away from the laminate, a low-pressure rapid mold closing method is adopted, and when the upper mold starts to contact the laminate, a high-pressure slow mold closing method is adopted; the pressure required for the low-pressure rapid mold closing is 1.5-3.0Mpa, and the pressure required for the high-pressure rapid mold closing is 15-30MPa.

10. The method according to claim 8, characterized in that In step S6, the inner wall of the box is first cleaned and polished, and then an ablation-resistant coating is formed by one of the following methods: First, apply the primer on the inner wall of the box or the upper cover, and then use the scraping method to attach the silicone rubber material to the inner wall of the box or the upper cover. After the scraping is completed, place it at 120-150℃ for 20-30s to cure; Alternatively, the fused quartz material is attached to the inner wall of the box or the upper cover by a scraping method, and the viscosity of the fused quartz material is controlled to be 60-70s during scraping, and after the scraping is completed, it is left to stand at room temperature for 60-80s to solidify; Alternatively, the RCG coating material may be attached to the inner wall of the box or the upper cover by spraying without curing.

Citation Information

Patent Citations

  • Manufacturing method of carbon fiber automobile battery box and carbon fiber automobile battery box

    CN105014988A

  • Forming method of carbon fiber battery box and carbon fiber battery box

    CN114536801A